Molecular imprinting and nanomaterial synergy for lactate detection - Christopher Animashaun; Gymama Slaughter (Biosensors and Bioelectronics: X)
Molecularly imprinted polymer (MIP)-based electrochemical sensors have emerged as promising non-enzymatic platforms for the selective and stable detection of clinically and environmentally relevant biomarkers. This review provides a critical, comprehensive analysis of recent advances in MIP-based lactate sensing, with particular emphasis on hybrid systems that integrate conductive nanomaterials including gold and silver nanoparticles, laser-induced graphene, and reduced graphene oxide. These synergistic combinations leverage enhanced surface area, electrical conductivity, and molecular recognition to improve sensor sensitivity, selectivity, and long-term operational stability. Key fabrication strategies, such as electropolymerization, green nanomaterial synthesis, and surface imprinting, are critically examined for their roles in optimizing imprinting sensitivity and electron transfer efficiency. Application areas span real-time lactate monitoring in wearable health devices to environmental surveillance in complex matrices. Despite significant progress, challenges related to reproducibility, template removal efficiency, fouling resistance, and scalable manufacturing persist. The review concludes by outlining future directions, including integration into flexible and paper-based platforms, and the development of smart, implantable systems. With continued innovation, MIP-based lactate sensors are poised to become essential components in next-generation point-of-care diagnostics and environmental monitoring technologies.